2012
DOI: 10.1590/s1516-35982012000200015
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of vegetable and mixed crude glycerin in the diet of growing rabbits

Abstract: -The objectives of this study were to determine the chemical composition of vegetable and mixed crude glycerin and digestible energy to and evaluate different inclusion levels in rabbit feeding. A total of 108 rabbits were used in the digestibility assay, assigned in a completely randomized design into nine treatments, one reference diet plus eight test diets, where the glycerin types were included at levels of 4, 8, 12 and 16%, replacing the reference diet roughage. In the performance assay, 180 rabbits were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Glycerol has been studied as a dietary energy source in several nonruminant animal cultures, such as poultry (Lima et al, 2012), swine (Shields et al, 2012), rabbit (Retore et al, 2012), and dogs (Lima et al, 2014). However, little is known about its inclusion in Nile tilapia (Oreochromis niloticus) diet.…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol has been studied as a dietary energy source in several nonruminant animal cultures, such as poultry (Lima et al, 2012), swine (Shields et al, 2012), rabbit (Retore et al, 2012), and dogs (Lima et al, 2014). However, little is known about its inclusion in Nile tilapia (Oreochromis niloticus) diet.…”
Section: Introductionmentioning
confidence: 99%
“…However, these additional procedures increase the cost (Min et al 2010). Thus, several studies on the inclusion of glycerin in its raw form in animal diets have been carried out to reduce the cost of production without affecting the performance (Jung and Batal 2011;Retore et al 2012). Additional advantages deriving from the use of crude glycerin in animal diets have also been reported, such as the improvement of growth, economic performance, and feed conversion ratio (Sehu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In broilers, Dozier et al (2008) found that the efficiency of energy use was approximately 95% of gross energy, depending on methanol, fatty acid, and glycerol contents of the sample (Dozier et al 2011), and the efficiency might vary according to the manufacturing process adopted (Retore et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Pure glycerol contains low amount of chemical residues and has been extensively used as a permeating cryoprotectant since Polge et al (1949) discovered its protective effects on cryopreserved spermatozoa. Crude glycerol is rich in fatty acids and contains chemical impurities such as methanol, sodium and potassium salts (Retore et al, 2012). Biodiesel industry is constantly producing crude glycerol as a by-product from biofuel fabrication through the NaOH-or KOH-catalysed transesterification of triacylglycerols (Ma and Hanna, 1999;Van Gerpen, 2005;Thompson and He, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The ready availability of crude glycerol makes it a promising alternative to the energy-rich diet used in animal nutrition, which could cover the energy needs of livestock (Kijora et al, 1995;Rosebrough et al, 1996;Simon et al, 1996;Cerrate et al, 2006). Therefore, numerous studies have focused on assessing the nutritional value of crude glycerol and optimizing its use in animal feeding (Retore et al, 2012). In non-ruminants, including rabbits, glycerol is absorbed through the gastrointestinal tract (Tao et al, 1983) and subsequently utilized as an energy source (Cryer and Bartley, 1973).…”
Section: Introductionmentioning
confidence: 99%